2016
DOI: 10.1590/0074-02760160104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Zika virus particles in cell cultures

Abstract: Zika virus (ZIKV) has infected thousands of Brazilian people and spread to other American countries since 2015. The introduction of ZIKV brought a strong impact to public health in Brazil. It is of utmost importance to identify a susceptible cell line that will enable the isolation and identification of the virus from patient samples, viral mass production, and testing of drug and vaccine candidates. Besides real-time reverse transcriptase polymerase chain reaction diagnosis for detecting the viral genome, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…Both control cells (Figure S2A‐B) and virus‐infected cells (Figures b, S2C‐D) contained numerous multivesicular bodies and multilamellar myelin‐like bodies. Although previous reports have suggested that these might be specific to ZIKV infection (Barreto‐Vieira, Barth, & Alexandre, ), the quantity and character of these two cellular components did not appear to be altered by infection in our experiments.…”
Section: Resultscontrasting
confidence: 82%
“…Both control cells (Figure S2A‐B) and virus‐infected cells (Figures b, S2C‐D) contained numerous multivesicular bodies and multilamellar myelin‐like bodies. Although previous reports have suggested that these might be specific to ZIKV infection (Barreto‐Vieira, Barth, & Alexandre, ), the quantity and character of these two cellular components did not appear to be altered by infection in our experiments.…”
Section: Resultscontrasting
confidence: 82%
“…The ultrastructure of a number of vector-borne flaviviruses has been well-studied (1825). There have been recent reports examining ZIKV infection in human skin cells (26) and African green monkey kidney cells (27). In addition papers have depicted ZIKV replication in cells of neural origin (28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…However, ZIKV morphogenesis remains controversial. Although it was previously shown to share similarities with the DENV cellular cycle 18 , ZIKV morphogenesis revealed differences from other members of its family. Additionally, the infection presents distinct dynamics in vertebrate and invertebrate cells, e.g., the presence of syncytia, which occurs only in C6/36-infected cells 19 .…”
mentioning
confidence: 99%